EMPOWERING STUDENTS IN IMPROVING THE ECONOMY OF PESANTREN THROUGH SUSTAINABLE WASTE MANAGEMENT - Anim Jauhariyah, Nur; Mahmudah, Mahmudah (Proceedings of Annual Conference on Community Engagement, 2023)
The objective of this service are 1) to record problems related to waste management in pesantren education units; 2) Provide empowerment in waste management in pesantren education units and TPS3R Kalisuro under the auspices of the of the Pesantren Darussalam Blokagung Banyuwangi. The mentoring method used is through the Participatory Action Research approach. The result of the service sho an increase in awareness with a percentage of 82.3% of education unit managers stating they are willing to form a Waste Bank. The weakness in waste management in pesatren is the limited technology ad management staff in sorting such larga amounts of waste, so there is still a lot of waste that can be sorted but is left as residue. Therefor, sorting waste form upstream or origin of waste is absolutely necessary.